A compact asymmetric slot dual band antenna fed by CPW for PCS and UWB applications. Issue 3 (18th September 2014) - Kumar, Raj; Naidu V, Praveen; Kamble, Vivek
ABSTRACT: A compact slot antenna with an overall dimension of 30 × 30 × 1.6 mm 3 is proposed for dual band applications. The radiating element is a hexagonal shape patch which protrudes from a Co‐Planar Waveguide (CPW) feed into a step shape slot. The slot is basically rectangular in shape and is extended by inserting rectangular cuts of different sizes on the ground plane around it. The ultrawide impedance bandwidth is achieved using asymmetric feed line along with extended rectangular cuts around the slot. For realizing the second band for personal communication system applications (near 1.9 GHz), a metallic stub of quarter wave length is attached at the top of the slot. The measured impedance bandwidth (for S 11 < −10 dB) is 110 MHz (1.86–1.97 GHz) for the first band and 9 GHz (3.0–12.0 GHz) for the second band. The antenna is further characterized by omnidirectional radiation patterns in the H ‐plane, dumb‐bell shape radiation patterns in the E ‐plane and a peak gain of 3–5 dBi over the ultrawideband. All the measured results are found to be in good agreement with the simulated results. © 2014 Wiley Periodicals, Inc. Int J RF and Microwave CAE 25:243–254, 2015.